2008
DOI: 10.1111/j.1365-2605.2007.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular dysgenesis syndrome and the origin of carcinoma in situ testis

Abstract: Recent increases in male reproductive disorders have been linked to exposure to environmental factors leading to the testicular dysgenesis syndrome (TDS). Testicular cancer is the most severe condition in TDS and studies have shown a clear correlation between risk of testicular cancer and other components of TDS and that the geographical location of the mother during pregnancy can be a risk factor. This suggests that the dysgenesis has its origin in utero and that TDS is initiated by environmental factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 125 publications
(218 reference statements)
2
41
0
4
Order By: Relevance
“…Testicular dysgenesis can be caused by impaired germ cell differentiation, hormone insufficiency, and dysfunction of Leydig and/or Sertoli cells (which both provide paracrine support) (23). The present study revealed marked differences in the structure and morphology of testes between Ppard ϩ/ϩ and Ppard Ϫ/Ϫ mice and elucidated a cooperative role of PPARD in Sertoli cells/germ cell interactions, thus demonstrating for the first time that PPARD Normal spermatid head shape is required for male fertility as demonstrated by previous studies (24 -28).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular dysgenesis can be caused by impaired germ cell differentiation, hormone insufficiency, and dysfunction of Leydig and/or Sertoli cells (which both provide paracrine support) (23). The present study revealed marked differences in the structure and morphology of testes between Ppard ϩ/ϩ and Ppard Ϫ/Ϫ mice and elucidated a cooperative role of PPARD in Sertoli cells/germ cell interactions, thus demonstrating for the first time that PPARD Normal spermatid head shape is required for male fertility as demonstrated by previous studies (24 -28).…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs should therefore not be interpreted as independent risk signals. (B) Global and schematic representation of the integrated role of genetic and environmental risk factors in the pathogenesis of TGCC inspired by the TDS model proposed by Sonne and colleagues [183].…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…TIN is found in testicular tissue adjacent to TGCNs in about 90% of cases, and it is observed in all clinical groups known to be at high risk for testicular cancer, including contralateral testis of patients with TGCN, cryptorchidism, infertility and ambiguous genitalia. If TIN is left untreated, there is a 50% probability of progressing to frank TGCN within 5 years and a 70% probability of developing malignancy within 7 years [3][4][5]7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Testicular germ cell neoplasms (TGCNs) constitute 90-95% of testicular tumors [1]. Testicular intraepithelial neoplasia (TIN) or intratubular germ cell neoplasia of unclassified type (ITGCNU) is considered the precursor of most TGCNs [2][3][4][5][6][7]. TIN is found in testicular tissue adjacent to TGCNs in about 90% of cases, and it is observed in all clinical groups known to be at high risk for testicular cancer, including contralateral testis of patients with TGCN, cryptorchidism, infertility and ambiguous genitalia.…”
Section: Introductionmentioning
confidence: 99%